PROFESSIONAL SELF-EDUCATIONAL ACTIVITIES OF STUDENTS - Bositkhonovich Rakhmonov, Azizkhon (International Journal of Psychosocial Rehabilitation, 2024)
the research article examines the structure of self-education, which is becoming a priority inthe development of modern pedagogy. For this purpose, self-education is correlated with thecategory of education, its philosophical, sociological and psychological interpretations aregiven. Based on the distinctive features, definitions of professional self-education in the selfeducational activities of students are given. In the article the author allocated and describedthe types, forms and components of self-education and self-education, depending on the depthof understanding of the object of self-education, the level of compliance of the content ofeducation, based on the orientation of the subject of activity and the degree of integration inthe professional sphere.